Nano anti-aging composition as well as preparation method and application thereof
By combining a variety of cosmetic ingredients into nano-anti-aging compositions and preparing them with high-pressure homogenization technology, the existing anti-aging cosmetics are solved, and the effects of multi-path coordinated regulation and long-term safe use are achieved, which significantly improves the skin firmness and anti-oxidation ability.
Patent Information
- Application Number
- CN202510249452.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-06-20
AI Technical Summary
Existing anti-aging cosmetics have limitations in single targets, insufficient stability and penetration, and long-term safety problems, making it difficult to achieve coordinated multi-channel regulation and long-term safe use.
By combining moisturizer, emulsifier, oil, oil-soluble active, water-soluble active and permeability into a nano-anti-aging composition, and preparing it using high-pressure homogenization technology, the stability and permeability of the composition are improved.
The effect of improving skin firmness and antioxidant is achieved, and the water solubility of oil-soluble active substances and the transdermal performance of nano-level anti-aging compositions are significantly improved, which enhances bioavailability and ensures safety.
Smart Images

Figure CN120168372A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, and in particular to a nano anti-aging composition, a preparation method thereof and an application thereof. Background Art
[0002] With the aggravation of population aging and consumers' attention to healthy lifespan, anti-aging research has become a hot topic in the fields of biomedicine, cosmetics and nutritional science. The core mechanisms of skin aging involve oxidative stress, mitochondrial function decline, extracellular matrix (ECM) degradation (such as loss of collagen and elastin), and chronic inflammatory responses, etc. Currently, the mainstream anti-aging strategies include: ① Antioxidant components (such as vitamin C, coenzyme Q10, resveratrol) delay oxidative damage by neutralizing free radicals; ② Cell repair and regeneration components (such as retinol, polypeptides, growth factors) stimulate collagen synthesis or promote epidermal renewal; ③ Anti-inflammatory and barrier repair components (such as ceramides, asiaticoside) relieve inflammation and strengthen the skin barrier function.
[0003] However, the existing technologies still have limitations: ① Single target limitation: Most components only target a certain physiological link of aging and it is difficult to achieve multi-pathway coordinated regulation; ② Insufficient stability and permeability: For example, vitamin C is easily oxidized and inactivated, and the transdermal absorption efficiency of large molecular polypeptides is low; ③ Long-term safety problems: Some potent components (such as high-concentration retinol) may cause irritation or photosensitivity reactions.
[0004] Therefore, there is an urgent need for an anti-aging cosmetic with excellent stability, permeability and good safety. Summary of the Invention
[0005] The purpose of the present invention is to overcome the deficiencies of the existing technologies and provide an anti-aging composition with excellent stability, permeability and good safety, a preparation method thereof and an application thereof.
[0006] To achieve the above purpose, the technical solutions adopted by the present invention are as follows:
[0007] In the first aspect, the present invention provides a nano anti-aging composition. In every 100 parts by mass of the nano anti-aging composition, it includes the following components in parts by mass: 1.0 - 65.0 parts of a humectant, 3.5 - 10.0 parts of an emulsifier, 0.1 - 5.0 parts of an oil, 0.1 - 30 parts of an oil-soluble active substance, 0.2 - 6.0 parts of a water-soluble active substance, and 0.2 - 5.0 parts of a penetration enhancer, and the solvent is supplemented to a total of 100 parts by mass.
[0008] The present invention combines a humectant, an emulsifier, an oil, an oil-soluble active substance, a water-soluble active substance, a solvent and a penetration enhancer into a nano anti-aging composition, which has the effects of improving skin firmness and antioxidant, and at the same time has good stability and safety, and can be applied in anti-aging cosmetics.
[0009] As a preferred embodiment of the nano anti-aging composition of the present invention, every 100 parts by mass of the nano anti-aging composition comprises the following components in parts by mass: 30.0 - 60.0 parts of a humectant, 4.0 - 6.0 parts of an emulsifier, 1.0 - 4.0 parts of an oil, 0.4 - 3.0 parts of an active substance, and 1.0 - 4.0 parts of a penetration enhancer, with the solvent being supplemented to a total of 100 parts by mass.
[0010] As a preferred embodiment of the nano anti-aging composition of the present invention, it comprises the following components in parts by mass: 60.0 parts of a humectant, 4.0 parts of an emulsifier, 1.0 part of an oil, 1.2 parts of an active substance, 31.8 parts of a solvent, and 3.0 parts of a penetration enhancer.
[0011] As a preferred embodiment of the nano anti-aging composition of the present invention, the emulsifier comprises at least one of polyglyceryl-10 laurate, hydrogenated lecithin, and PEG-40 hydrogenated castor oil. The present invention preferably uses polyglyceryl-10 laurate and hydrogenated lecithin as emulsifiers. Through high-pressure homogenization technology, the emulsifier can be more fully mixed with other components, making the nano anti-aging composition transparent and having good stability.
[0012] As a preferred embodiment of the nano anti-aging composition of the present invention, the emulsifier comprises polyglyceryl-10 laurate and hydrogenated lecithin, and the mass ratio of polyglyceryl-10 laurate to hydrogenated lecithin is polyglyceryl-10 laurate:hydrogenated lecithin = (0.3 - 50):1.0.
[0013] As a preferred embodiment of the nano anti-aging composition of the present invention, the mass ratio of polyglyceryl-10 laurate to hydrogenated lecithin is polyglyceryl-10 laurate:hydrogenated lecithin = (3.0 - 5.0):1.0.
[0014] As a preferred embodiment of the nano anti-aging composition of the present invention, the mass ratio of polyglyceryl-10 laurate to hydrogenated lecithin is polyglyceryl-10 laurate:hydrogenated lecithin = 3.0:1.0.
[0015] As a preferred embodiment of the nano anti-aging composition of the present invention, the oil-soluble active substance comprises teprenone. Teprenone is a terpene derivative and has effects such as protecting and repairing the skin, antioxidant, and anti-inflammatory in cosmetics.
[0016] As a preferred embodiment of the nano anti-aging composition of the present invention, the water-soluble active substance includes at least one of sodium DNA and Rhododendron arboreum extract. Sodium DNA (also known as PDRN) has functions such as moisturizing, antioxidant, soothing and repairing, etc., and can further improve the anti-aging effect when combined with other components. The Rhododendron arboreum extract contains active substances such as flavonoids and polysaccharides, which can effectively scavenge free radicals in the body, slow down the oxidation state, maintain cell health, and further improve the anti-aging effect of the composition when combined with other components.
[0017] As a preferred embodiment of the nano anti-aging composition of the present invention, the mass ratio of sodium DNA to Rhododendron arboreum extract in the water-soluble active substance is sodium DNA: Rhododendron arboreum extract = 1.0: (0.03 - 30).
[0018] As a preferred embodiment of the nano anti-aging composition of the present invention, the mass ratio of sodium DNA to Rhododendron arboreum extract in the water-soluble active substance is sodium DNA: Rhododendron arboreum extract = 1.0: (1.0 - 10.0).
[0019] The mass ratio of sodium DNA to Rhododendron arboreum extract in the water-soluble active substance is sodium DNA: Rhododendron arboreum extract = 1:2.5.
[0020] As a preferred embodiment of the nano anti-aging composition of the present invention, the humectant includes at least one of glycerol, 1,3-butanediol, and 1,3-propanediol.
[0021] As a preferred embodiment of the nano anti-aging composition of the present invention, the oil includes at least one of squalane, olive oil, and jojoba seed oil.
[0022] As a preferred embodiment of the nano anti-aging composition of the present invention, the solvent includes at least one of the filtrate of Saccharomycopsis ferment and the filtrate of Saccharomyces boulardii ferment. Using the filtrate of Saccharomycopsis ferment instead of water as the solvent can effectively improve the anti-aging effect of the nano anti-aging composition.
[0023] As a preferred embodiment of the nano anti-aging composition of the present invention, the penetration enhancer includes at least one of bis-diethoxydiglycol cyclohexane 1,4-dicarboxylate, isobutyl oleate, and ethoxydiglycol. Bis-diethoxydiglycol cyclohexane 1,4-dicarboxylate is a penetration enhancer with an amphiphilic structure, which can penetrate deep into the intercellular lipids, briefly open channels, promote the penetration effect of water-soluble and oil-soluble active substances, and thus enhance the efficacy of the nano anti-aging composition.
[0024] As a preferred embodiment of the nano anti-aging composition of the present invention, the nano anti-aging composition is in the form of an emulsion, and the emulsion particle size is 10 - 100 nm.
[0025] As a preferred embodiment of the nano anti-aging composition of the present invention, the nano anti-aging composition is in the form of an emulsion, and the emulsion particle size is 20-80 nm.
[0026] In a second aspect, the present invention provides a method for preparing the above-mentioned nano anti-aging composition, comprising the following steps:
[0027] (1) Mix a humectant, an emulsifier, an oil and an oil-soluble active ingredient at 80-85 °C to obtain phase A;
[0028] (2) Homogeneously mix the solvent and phase A obtained in step (1) at 80-85 °C to obtain mixture A;
[0029] (3) When the temperature of mixture A obtained in step (2) drops to 40-45 °C, add a penetration enhancer and a water-soluble active ingredient, maintain the temperature at 40-45 °C for mixing, and perform high-pressure homogenization to obtain the nano anti-aging composition. The water solubility of the oil-soluble active ingredient teprenone in the nano anti-aging composition of the present invention is poor and it is difficult to be applied in an aqueous agent system. However, through the high-pressure homogenization technology of the present invention, the water solubility of teprenone can be effectively enhanced, enabling it to be applied in an aqueous agent system, greatly broadening the application scope of teprenone.
[0030] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention, (a) in step (1), the mixing is carried out by stirring at 100-300 rpm for 10-15 min.
[0031] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention, in step (2), the homogeneous mixing is carried out by homogenizing at 8000-15000 rpm for 3-5 min.
[0032] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention, in step (3), the mixing is carried out by stirring at 100-300 rpm for 10-15 min.
[0033] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention, in step (3), the high-pressure homogenization is carried out by circulating and homogenizing at 13000-17000 PSI for 2-5 times, and the homogenization time for each time is 3-5 min.
[0034] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention, in step (3), the high-pressure homogenization is carried out by circulating and homogenizing at 15000 PSI for 2-5 times, and the homogenization time for each time is 3-5 min.
[0035] As a preferred embodiment of the method for preparing the nano anti-aging composition of the present invention,
[0036] Thirdly, the present invention provides an application of the above-mentioned nano anti-aging composition in the preparation of anti-aging cosmetics.
[0037] Fourthly, the present invention provides an anti-aging cosmetic, comprising the above-mentioned nano anti-aging composition and excipients.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] (1) By mixing a humectant, an emulsifier, an oil, an active substance, a solvent and a penetration enhancer and subjecting the mixture to high-pressure homogenization, the present invention prepares a nano anti-aging composition, which has the effects of improving skin firmness and antioxidant, and thus realizes the anti-aging effect.
[0040] (2) By treating the nano anti-aging composition with high-pressure homogenization technology, the present invention significantly improves the water solubility of oil-soluble active substances. At the same time, the nano-scale anti-aging composition has better transdermal performance, is easily absorbed by the skin, and can effectively improve the bioavailability. Description of the Drawings
[0041] Figure 1 It is the particle size distribution diagram of the nano anti-aging composition obtained in Example 10 of the present invention;
[0042] Figure 2 It is the stability test result of different nano anti-aging compositions in Effect Example 1 of the present invention;
[0043] Figure 3 It is the skin firmness test result of different nano anti-aging compositions in Effect Example 2 of the present invention. Detailed Embodiments
[0044] To better illustrate the purpose, technical solution and advantages of the present invention, the present invention will be further described below with reference to specific embodiments.
[0045] Other materials, reagents, etc. used in the examples, comparative examples and effect examples can be obtained from commercial channels without special instructions.
[0046] The teprenone in the following examples and comparative examples was purchased from Guangzhou Aoyuan Trading Co., Ltd., and the product name was Renovage MBAL;
[0047] The filtrate of galactomyces ferment filtrate was purchased from Guangzhou Youke Biotechnology Co., Ltd.;
[0048] Bis-diethoxydiglycol cyclohexane-1,4-dicarboxylate was purchased from Shanghai Hongji Enterprise Development Co., Ltd.,
[0049] The product name was Neosolue-Aqulio, and the CAS number was 922165-31-9;
[0050] The sodium DNA was purchased from Runhui Biotechnology (Weihai) Co., Ltd., and the product name is polydeoxyribonucleotide (PDRN).
[0051] The extract of Rhododendron arboreum, also known as the extract of Rhododendron arboreum flowers, was purchased from Guangzhou Dingyue Biotechnology Co., Ltd.
[0052] Examples 1-10 and Comparative Examples 1-3
[0053] Examples 1-13 respectively provided a nano anti-aging composition and its preparation method. The components and their dosages of the nano anti-aging composition are shown in Table 1. The preparation method includes the following steps:
[0054] S1. Mix the humectant, emulsifier, oil and oil-soluble active substances at 80-85 °C and 100-300 rpm to obtain Phase A.
[0055] S2. Homogenize and mix the solvent and Phase A obtained in Step S1 at 80-85 °C and 8000-15000 rpm for 3-5 min to obtain Mixture A.
[0056] S3. Adjust the stirring speed to 100-300 rpm. When the temperature of Mixture A obtained in Step S2 drops to 40-45 °C, add the penetration enhancer and water-soluble active substances, and keep the temperature at 40-45 °C and the speed at 100-300 rpm and stir for 10-15 min to mix, obtaining Mixture B.
[0057] S4. Circulate and homogenize Mixture B obtained in Step S3 at 15000 PSI for 2-5 times, 3-5 min each time, to obtain the nano anti-aging composition.
[0058] The particle size of the nano anti-aging composition obtained in Example 10 was tested, and the results are as Figure 1 shown in Table 2. The particle size of the obtained nano anti-aging composition is 10-80 nm, and the average particle size is about 20 nm.
[0059] Table 1 Components and their dosages (parts by mass) of different nano anti-aging compositions
[0060]
[0061]
[0062] Table 2 Test results of the particle size distribution of the nano anti-aging composition obtained in Example 10
[0063] Group Average value Z - mean (nm) 20.01 Polydispersity index (PI) 0.1022 Average counting rate (kcps) 108.2 Mean value of peak 1 of particle size light intensity distribution sorted by area (nm) 21.05 Intercept 0.9831 Fitting error 0.0008193
[0064] Comparative Example 4
[0065] Comparative Example 4 provides a nano anti-aging composition and a preparation method thereof. The components and their dosages of the nano anti-aging composition are the same as those in Example 10, and the preparation method is similar to that in Example 10. The difference is that high-pressure homogenization is not carried out, and the mixture B obtained in step S3 is the nano anti-aging composition.
[0066] Comparative Examples 5-10
[0067] Comparative Examples 5-10 respectively provide a nano anti-aging composition and a preparation method thereof. The components and their dosages of the nano anti-aging composition are shown in Table 3, and the preparation method is the same as that in Example 10.
[0068] Table 3 Components and Dosages (parts by mass) of Different Nano Anti-aging Compositions
[0069]
[0070] Effect Example 1
[0071] The nano anti-aging compositions obtained in Examples 1-10 and Comparative Examples 1-10 were subjected to a stability test. The specific scheme is as follows:
[0072] 30 g of the nano anti-aging compositions obtained in Examples 1-10 and Comparative Examples 1-10 were respectively placed in an incubator at 48 °C or -15 °C. The state of the nano anti-aging compositions was observed every month. The results are shown in Table 4, and the product pictures of some nano anti-aging compositions are shown in Figure 3 .
[0073] Table 4 Stability Test Results of Different Nano Anti-aging Compositions
[0074] Group Room temperature Heat - resistant at 48°C Cold - resistant at - 15°C Example 1 Milky white No stratification for 3 months No stratification for 3 months Example 2 Milky white No stratification for 3 months No stratification for 3 months Example 3 Semi - transparent liquid No stratification for 3 months No stratification for 3 months Example 4 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 5 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 6 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 7 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 8 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 9 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Example 10 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 1 Colorless transparent liquid Stratified in 1 month Stratified in 1 month Comparative Example 2 Colorless transparent liquid Stratified in 1 month Stratified in 1 month Comparative Example 3 Colorless transparent liquid Stratified in 2 months Stratified in 2 months Comparative Example 4 Milky white Stratified in 2 weeks Stratified in 3 weeks Comparative Example 5 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 6 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 7 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 8 Yellow transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 9 Colorless transparent liquid No stratification for 3 months No stratification for 3 months Comparative Example 10 Colorless transparent liquid No stratification for 3 months No stratification for 3 months
[0075] From Figure 3As shown in Table 4, according to Examples 1-4 and Comparative Example 1 in Table 4, the higher the glycerol addition amount, the more transparent the appearance of the composition. When the glycerol content in every 100 parts by mass of the nano anti-aging composition exceeds 60 parts by mass, the composition still presents a colorless and transparent liquid appearance, but the stability decreases. When the glycerol mass fraction in every 100 parts by mass of the nano anti-aging composition reaches 70 parts, layering occurs during heat resistance and cold resistance tests for 1 month, and the stability deteriorates. It is comprehensively concluded that when the glycerol mass fraction in every 100 parts by mass of the nano anti-aging composition is 60 parts, its appearance and stability are optimal. By comparing Example 4 with Comparative Examples 2-3 and Examples 5-6, it can be seen that the higher the addition amount of polyglyceryl-10 laurate, the better the stability of the composition. When its addition amount in every 100 parts by mass of the nano anti-aging composition ≥ 3 parts by mass, the composition can meet the 3-month stability investigation. Considering from the cost perspective, Example 4 is superior to Examples 5 and 6. Comparative Example 4 has the same formulation as Example 10, the difference is that Comparative Example 4 uses the traditional emulsification and homogenization process for preparation, and only completes steps S1-S3 of the preparation method. By observing the stability, it can be obtained that the nano anti-aging composition prepared by the special process of high-pressure homogenization technology is superior to the traditional emulsification process in both appearance and stability.
[0076] Effect Example 2
[0077] The nano anti-aging compositions obtained from Examples 4, 7-10 and Comparative Examples 4-10 were subjected to skin firmness tests, and the specific scheme is as follows:
[0078] In this experiment, a skin elasticity tester Cutometer dual MPA580 was used to test skin firmness. Skin firmness means that the skin is elastic and full of collagen. The increase or decrease of skin firmness is closely related to skin elasticity and the collagen content in the skin. When the skin is loose and collagen is lost, the value of skin firmness increases. When the skin is elastic and full of collagen, the value of skin firmness decreases accordingly. The RO value of skin firmness was measured using MPA580. The RO value reflects the passive feedback of the skin to external forces. The smaller the R0 value, the firmer the skin.
[0079] Test environment: The temperature is 22±1°C and the humidity is 50±5%, and real-time dynamic detection is carried out;
[0080] Test volunteers: Aged between 30-45 years old (excluding pregnant or lactating women), 60 people, without serious systemic diseases, immune deficiencies or autoimmune diseases; those with no serious allergic history to skin care cosmetics in the past; those who have not used hormonal drugs and immunosuppressants in the past month; those who have not participated in other clinical trials; those who use the test drug as required and have complete information; all volunteers filled out an informed consent form before the test.
[0081] Preparation before the test: Do not use any products (cosmetics or topical medications) on the test area 2 - 3 days before the test.
[0082] Test process: There are 60 subjects, 5 in each group, divided into 12 groups, corresponding to Example 4, Examples 7 - 10, and Comparative Examples 4 - 10 respectively. The subjects clean their faces and sit quietly in a constant temperature and humidity chamber for 30 minutes, and the skin firmness of their cheeks is measured as the original value. Then, according to their daily usage habits, the product is taken and applied to the entire face, gently massaged until completely absorbed, and then the product usage instructions are given and the product is distributed for subsequent use. The subjects need to use it once in the morning and once in the evening every day for 28 consecutive days, and then return to the laboratory for testing again. The tests for the same volunteer are completed by the same measurement personnel.
[0083] The measurement parameters are set as: ON - TIME: 1.0S, OFF - TIME: 1.0S, Pressure: 450mbar, Repetition: 10. The average value of 5 people in each group is taken for each test.
[0084] Calculate the skin firmness improvement rate from the test results. The results are shown in Table 5 and Figure 3 , and the calculation formula for the skin firmness improvement rate is as follows:
[0085] R%=(RO2 - RO1) / RO1×100%
[0086] In the formula, R is the skin firmness improvement rate, %; RO1 is the original value of skin firmness before using the sample; RO2 is the skin firmness value after continuously using the sample for 28 days.
[0087] Table 5 Test results of skin firmness of different nano anti - aging compositions
[0088] Group RO1 RO2 R% Example 4 0.25 0.22 -12.00 Example 7 0.20 0.17 -15.00 Example 8 0.22 0.18 -18.18 Example 9 0.24 0.19 -20.83 Example 10 0.26 0.18 -30.77 Comparative Example 4 0.17 0.15 -11.76 Comparative Example 5 0.16 0.15 -6.25 Comparative Example 6 0.18 0.16 -11.11 Comparative Example 7 0.2 0.18 -10.00 Comparative Example 8 0.21 0.17 -19.05 Comparative Example 9 0.22 0.18 -18.18 Comparative Example 10 0.20 0.16 -20.00
[0089] Such as Figure 3As shown in Table 5, by comparing Example 4 with Examples 7 - 10, it can be seen that as the content of teprenone increases, the skin firmness gradually improves, showing a gradually enhanced anti - aging effect. The only difference between Example 10 and Comparative Example 4 is that the preparation method of Comparative Example 4 only completed steps S1 - S3 and did not undergo high - pressure homogenization treatment. From the experimental data, it can be obtained that the particle size of the anti - aging composition after high - pressure homogenization treatment reaches the nanoscale, with better transdermal permeability, which can further improve the anti - aging effect of the composition. By comparing Example 10 with Comparative Examples 5 - 7, it can be seen that teprenone, sodium DNA, and Rhododendron arboreum extract all have an impact on skin firmness, and there is a synergistic enhancement effect among them. By comparing Example 10 with Comparative Examples 8 - 10, it can be seen that the skin firmness data measured after replacing teprenone with the same - type raw material hydroxy pinacolone retinoate, sodium DNA with the same - type raw material hydroxypropyl tetrahydropyran triol, and Rhododendron arboreum extract with the same - type raw material Centella asiatica extract are all lower than those of Example 10. It can be seen that only when specific ratios, specific types of active substances are combined with humectants, emulsifiers, oils, solvents, and penetration enhancers to form a nano anti - aging composition can excellent anti - aging efficacy be achieved.
[0090] Effect Example 3
[0091] The nano anti - aging compositions obtained from Examples 4, 7 - 10, and Comparative Examples 4 - 10 were tested for their free - radical scavenging ability. The specific scheme is as follows:
[0092] 1. Prepare a 0.1 mmol / L DPPH solution with absolute ethanol (1 mg DPPH is dissolved in 24 mL of absolute ethanol), ultrasonicate for 5 min, shake well, store in the dark, and use it up within 5 h.
[0093] 2. Add 2 mL of the test sample solution (the sample is dissolved with absolute ethanol) and 2 mL of the DPPH solution into the same test tube, shake well, let it stand in the dark at room temperature for 30 min, and then measure its absorbance Asample. Repeat 3 times, mark them as A1, A2, and A3 respectively, and take the average value. At the same time, measure the absorbance A0 after mixing 2 mL of the DPPH solution and 2 mL of ethanol as the blank group, repeat 3 times as well, and take the average value.
[0094] 3. Calculate the free - radical scavenging ability of the sample according to the following formula:
[0095] DPPH scavenging percentage = (A0 - Asample) / A0 × 100
[0096] In the formula, A0 is the absorbance of DPPH at 520 nm without adding the sample; Asample is the absorbance of DPPH at 520 nm after adding the sample.
[0097] The results are shown in Table 6.
[0098] Table 6 Test Results of Free Radical Scavenging Ability of Different Nano Anti-aging Compositions
[0099]
[0100]
[0101] From the experimental results in Table 6, it can be seen that both the examples and the comparative examples have a certain antioxidant effect. However, the antioxidant effects of Examples 4 and 7-10 are significantly better than those of Comparative Examples 4-10. Since Comparative Example 4 only differs from Example 10 in the preparation process, there is no significant difference in the DPPH free radical scavenging rate. Combining the above experimental results, it is found that Example 10 has the best antioxidant effect, with an obvious antioxidant effect, which can resist the damage of free radicals to the skin and achieve a better anti-aging effect.
[0102] Effect Example 4
[0103] The nano anti-aging compositions obtained in Examples 4 and 7-10 were subjected to safety evaluation, and the specific scheme is as follows:
[0104] The human patch test was used for evaluation.
[0105] 1. Test method: A total of 30 subjects, with the specific gender and age compositions randomly determined (meeting the inclusion and exclusion criteria of the "Diagnostic Criteria and Management Principles for Cosmetic Contact Dermatitis"). The samples prepared in Examples 4 and 7-10 were placed in the patch tester (the sample dosage was 0.020 - 0.025 g), and the control hole was blank (without any substance). The samples and the blank control were both applied to the flexor side of the forearm of the subjects, and gently pressed with the palm to make them evenly adhere to the skin for 24 h. 30 minutes after removing the patch tester, after the indentation disappeared, the skin reaction was observed. If the result was negative, it was observed again at 24 h and 48 h respectively, and the results are shown in Table 8.
[0106] According to the "Diagnostic Criteria and Management Principles for Cosmetic Contact Dermatitis", the classification and judgment criteria are shown in Table 7. The judgment criterion is that when the number of subjects with grade 1 skin adverse reactions after 24 h of patch testing among 30 subjects is more than 5 cases, or the number of subjects with grade 2 skin adverse reactions is more than 2 cases, or any 1 case of grade 3 or above skin adverse reaction occurs, it is determined that the test substance has skin adverse reactions to humans.
[0107] Table 7 Diagnostic Criteria for Cosmetic Contact Dermatitis
[0108]
[0109]
[0110] Table 8 Patch Test Results of Different Nano Anti-aging Compositions
[0111]
[0112] As can be seen from Table 8, Example 4 and Examples 7 - 10 have all undergone patch tests, and it is determined that they have no adverse reactions to human skin, indicating that the nano anti - aging composition of the present invention has good safety and is not likely to cause contact dermatitis to the skin.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A nano anti-aging composition, characterized in that: Every 100 parts by mass of the nano anti-aging composition includes the following components in parts by mass: 1.0-65.0 parts by mass of moisturizer, 3.5-10.0 parts by mass of emulsifier, 0.1-5.0 parts by mass of oil, 0.1-3.0 parts by mass of oil-soluble active substance, 0.2-6.0 parts by mass of water-soluble active substance and 0.2-5.0 parts by mass of penetration enhancer, and the solvent is supplemented to a total of 100 parts by mass.
2. The nano anti-aging composition according to claim 1, characterized in that: Every 100 parts by weight of the nano anti-aging composition includes the following components in parts by weight: 30.0-60.0 parts by weight of moisturizer, 4.0-6.0 parts by weight of emulsifier, 1.0-4.0 parts by weight of oil, 0.2-2.0 parts by weight of oil-soluble active ingredient, 0.4-3.0 parts by weight of water-soluble active ingredient and 1.0-4.0 parts by weight of penetration enhancer, and the solvent is supplemented to a total of 100 parts by weight.
3. The nano anti-aging composition according to claim 1, characterized in that: The emulsifier includes at least one of polyglyceryl-10 laurate, hydrogenated lecithin, and PEG-40 hydrogenated castor oil.
4. The nano anti-aging composition according to claim 3, characterized in that: The emulsifier comprises polyglyceryl-10 laurate and hydrogenated lecithin, and the mass ratio of polyglyceryl-10 laurate to hydrogenated lecithin is polyglyceryl-10 laurate: hydrogenated lecithin=(0.3-50.0):1.
0.
5. The nano anti-aging composition according to claim 1, characterized in that: Including at least one of the following (I) to (II): (I) the oil-soluble active ingredient includes teprenone; (II) The water-soluble active ingredient includes at least one of sodium DNA and Rhododendron arborescens extract.
6. The nano anti-aging composition according to claim 5, characterized in that: The mass ratio of DNA sodium and Rhododendron arborea extract in the water-soluble active substance is DNA sodium: Rhododendron arborea extract=1.0:(0.03-30.0).
7. The nano anti-aging composition according to claim 1, characterized in that: Including at least one of the following (III) to (VII): (III) the humectant comprises at least one of glycerol, 1,3-butylene glycol, and 1,3-propylene glycol; (IV) the oil comprises at least one of squalane, olive oil, and jojoba seed oil; (V) the solvent comprises at least one of a filtrate of a fermentation product of galactosaccharomyces cerevisiae and a filtrate of a fermentation product of bifid yeast; (VI) the penetration enhancer comprises at least one of bis-diethoxydiglycol cyclohexane 1,4-dicarboxylate, isobutyl oleate and ethoxydiglycol; (VII) The nano anti-aging composition is in the form of an emulsion, and the particle size of the emulsion is 10-100 nm.
8. The method for preparing the nano anti-aging composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing a moisturizer, an emulsifier, a fat and an oil-soluble active ingredient at 80-85° C. to obtain a phase A; (2) homogeneously mixing the solvent and the phase A obtained in step (1) at 80-85° C. to obtain a mixture A; (3) When the temperature of the mixture A obtained in step (2) drops to 40-45° C., a penetration enhancer and a water-soluble active ingredient are added, the temperature is maintained at 40-45° C., and the mixture is mixed and homogenized under high pressure to obtain a nano anti-aging composition.
9. The method for preparing the nano anti-aging composition according to claim 8, characterized in that: Including at least one of the following (a) to (c): (a) In step (1), the mixing is performed by stirring at 100-300 rpm for 10-15 min; (b) In step (2), the homogenizing and mixing is performed at 8000-15000 rpm for 3-5 min; (c) in step (3), the mixing is performed by stirring at 100-300 rpm for 10-15 min; (d) In step (3), the high pressure homogenization is performed at 13000-17000 PSI for 2-5 cycles, and each homogenization time is 3-5 minutes.
10. Use of the nano anti-aging composition according to any one of claims 1 to 7 in the preparation of anti-aging cosmetics.